Environmental Risk and Management of Herbal-Extraction Residues Induced by the Composition and Metal Binding Properties of DOM - Yuan, Donghai; Cui, Yanqi; Kou, Yingying; Guo, Xujing; Chen, Bin (Frontiers in Environmental Science, 2022)
With the consumption of Chinese medicine resources increases, and the waste of traditional Chinese medicine extraction can not be disposed reasonably, which has a serious impact on the environment. Dissolved organic matter (DOM), a crucial fraction in herbal-extraction residue, can bond onto heavy metals (HMs), creating a potential environmental risk. This study investigated the binding property of herbal-extraction residue DOM with Cu(II) via two-dimensional Fourier Transform Infrared (FTIR) and synchronous fluorescence correlation spectroscopy (2D-COS) in conjunction with parallel factor (PARAFAC) modeling. Through PARAFAC analysis, three kinds of protein components and one kind of fulvic acid can be obtained, and protein-like substances are dominant in the residual DOM of Chinese medicine extracts, becoming the main factor of water quality deterioration. Fluorescence quenching experiment shows that protein-like materials provide the primary binding sites with Cu(II). During the detection, the long wavelength low-intensity signal will be obscured. The 2d-cos obtained by 1 / 9th power transformation can enhance the fluorescence signal, so as to get even more content about the binding sites and heterogeneity of DOM and heavy metal ion ligands. The N−H of amine in the protein-like materials could priority combine with Cu(II). This study urges that continuous and effective attention be paid to the impact of herbal-extraction residue on the geochemical behavior of HMs.